2014
DOI: 10.5194/acp-14-11587-2014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of OMI operational standard NO<sub>2</sub> column retrievals using in situ and surface-based NO<sub>2</sub> observations

Abstract: Abstract. We assess the standard operational nitrogen dioxide (NO 2 ) data product (OMNO2, version 2.1) retrieved from the Ozone Monitoring Instrument (OMI) onboard NASA's Aura satellite using a combination of aircraft and surface in situ measurements as well as ground-based column measurements at several locations and a bottom-up NO x emission inventory over the continental US. Despite considerable sampling differences, NO 2 vertical column densities from OMI are modestly correlated (r = 0.3-0.8) with in situ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
186
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 209 publications
(196 citation statements)
references
References 105 publications
(124 reference statements)
10
186
0
Order By: Relevance
“…We exclude observations from the first and last cross-track positions, those that fail the retrieval algorithm statistical quality checks, and those impacted by the row anomaly (http://www.knmi.nl/omi/research/product/ rowanomaly-background.php). Validation with aircraft data indicates that the OMI HCHO and NO 2 retrievals are accurate within 20 and 30 %, respectively (Lamsal et al, 2014;Zhu et al, 2016). CHOCHO/HCHO column ratios from OMI are consistent with aircraft observations (Kaiser et al, 2015), whereas previous SCIAMACHY retrievals showed large discrepancies (DiGangi et al, 2012).…”
Section: Methodssupporting
confidence: 57%
“…We exclude observations from the first and last cross-track positions, those that fail the retrieval algorithm statistical quality checks, and those impacted by the row anomaly (http://www.knmi.nl/omi/research/product/ rowanomaly-background.php). Validation with aircraft data indicates that the OMI HCHO and NO 2 retrievals are accurate within 20 and 30 %, respectively (Lamsal et al, 2014;Zhu et al, 2016). CHOCHO/HCHO column ratios from OMI are consistent with aircraft observations (Kaiser et al, 2015), whereas previous SCIAMACHY retrievals showed large discrepancies (DiGangi et al, 2012).…”
Section: Methodssupporting
confidence: 57%
“…This is the case for NO 2 , SO 2 , and HCHO as their chemical lifetimes are short and their primary sources are located near the Earth's surface. As an example, Lamsal et al (2015) show that the long-term trends and short-term monthly variations in OMI NO 2 column densities from 2005 to 2013 compare well (e.g., r = 0.68 for trends) with those from the majority of surface concentration observations from the U.S. Environmental Protection Agency's (EPA) Air Quality System (AQS). Lamsal et al (2015) argue that the spatial coverage afforded by the OMI satellite data in combination with the maturity of the current retrieval algorithm allows for a more representative estimation of NO 2 trends within a city than observations from a sparse network of surface monitors.…”
Section: Omi Data Productsmentioning
confidence: 92%
“…GEOS-Chem concentrations of NO 2 and H 2 O 2 (proxy for HO 2 ) have been evaluated successfully in a number of aircraft campaigns (Martin et al, 2006;Hudman et al, 2007;Singh et al, 2007;Lin and McElroy, 2010;Mao et al, 2010;Travis et al, 2016). GEOS-Chem NO 2 columns have also been evaluated against satellite observations over China (Lin et al, 2012), North America (e.g., Lamsal et al, 2014), and Africa (Marais et al, 2012). Fast Hg 0 oxidation in the polar spring boundary layer is simulated by specifying high BrO concentrations when conditions for temperature, sea ice cover, sunlight, and atmospheric stability are met .…”
Section: Atmospheric Chemistrymentioning
confidence: 99%